Estratégia de controle para um processo de flotação por ar dissolvido (FAD) de separação àgua-óleo. - Galdino, Rodrigo Almeida (2017)
The state of Pernambuco is becoming increasingly industrialized and diversified array, with projects in the areas of petroleum refining, petrochemical, steel, shipbuilding and offshore industry, automotive, and electrical equipment. In the current global context, where one strives for environmental preservation, the major challenge faced by these large developments has been to ensure the quality and continuous development of its processes without compromising local environmental quality. Therefore it is of paramount importance to reduce the amount and / or improve the quality of wastewater generated by various industries and their production processes. The systems of dissolved air flotation (DAF) are more compact than alternative systems in water-oil separation, and they allow the recovery of raw materials in the treatment of these industrial effluents. In this sense, the goal of this project is to develop an effective strategy for automation and process control for a type of FAD, in the treatment of oily waters. The findings demonstrate that it is possible to maintain the level of the fluid at a reference value established by the operator using the software program LabVIEW through the application of classic proportional integral derivative controllers. Using this control tool, the efficiency of water-oil separation in the pilot flotation chamber prototype was increased to nearly 98%.